2014
DOI: 10.1053/j.ajkd.2013.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation and Outcomes of Cardiovascular Implantable Electronic Device Infections in Hemodialysis Patients

Abstract: Background Infection is a serious complication of cardiovascular implantable electronic device (CIED) implantation. Kidney failure is as an independent risk factor for CIED infection and associated mortality. The presence of multiple comorbid conditions may contribute to varied clinical presentations and poor outcomes in hemodialysis (HD)–dependent patients with cardiac device infection. Study Design Case series. Setting & Participants CIED infections in HD patients (n=17) and non-HD patients (n=398) at Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…Despite strict aseptic precautions at implantation, two patients developed infection requiring explant (two weeks and three months post implant respectively); this reflects the general susceptibility of dialysis patients to procedure related infections. [ 27 ] The Reveal XT is particularly sensitive for the detection of AF. Yet AF was incorrectly identified in many transmissions due to T wave over sensing resulting from intermittent deep T wave inversion, under sensing of R waves following a drop in the size of recorded QRS complexes, as well as noise/interference.…”
Section: Discussionmentioning
confidence: 99%
“…Despite strict aseptic precautions at implantation, two patients developed infection requiring explant (two weeks and three months post implant respectively); this reflects the general susceptibility of dialysis patients to procedure related infections. [ 27 ] The Reveal XT is particularly sensitive for the detection of AF. Yet AF was incorrectly identified in many transmissions due to T wave over sensing resulting from intermittent deep T wave inversion, under sensing of R waves following a drop in the size of recorded QRS complexes, as well as noise/interference.…”
Section: Discussionmentioning
confidence: 99%
“…The previous factors highlight why diagnosis is difficult and often subject to delay. Time from symptom onset to diagnosis for all identified cases of Propionibacterium CIED‐related IE (mean, 74 days [±83]) was twice longer than what is previously described for CIED‐IE (mean, 36 days [±117]) . Delay in diagnosis may lead to undesirable complications.…”
Section: Discussionmentioning
confidence: 97%
“…[ 26 ] The rate of SCD in dialysis patients, 41 per 1000 person-years in our study, was substantially higher than that reported in the general population [ 27 ]. Implantable cardioverter-defibrillators (ICDs) can prevent SCD but are associated with a higher risk of infection [ 28 , 29 ]. There are no randomized controlled data to guide primary prevention ICDs in this high risk population.…”
Section: Discussionmentioning
confidence: 99%